2021
DOI: 10.3389/fphys.2021.608056
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Exposure to 4-Nonylphenol Alters UDP-Glycosyltransferase and Sulfotransferase Clearance of Steroids in the Hard Coral, Pocillopora damicornis

Abstract: The effects of the xenoestrogen 4-nonylphenol (4NP) on endocrine and metabolic homeostasis in the reef building coral, Pocillopora damicornis were investigated. The aim was to understand if ubiquitous nonylphenol ethoxylate contaminants in the marine environment result in altered homeostatic function. Coral colonies were chronically exposed (6 weeks) to a sublethal concentration (1 ppb) of 4NP and sampled over the coral’s lunar reproductive cycle. Although activity of steroidogenic enzymes [cytochrome P450 (CY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…For example, Meng et al (2022) tested human urinalysis strips on corals and found that ketone and leukocytes were reliably detected by the strips. Some of the proteins that were upregulated in corals exposed to reduced water quality, particularly toxicants, such as pesticides and polycyclic aromatic hydrocarbons (PAHs) ubiquitously detected in this study, are steroidal clearance/detoxification and regeneration enzymes that also play a role in reproduction (Rougée et al, 2006;Rougée et al, 2015;Rougée et al, 2021). Just as coral colony energetic allocation to maintenance and repair can compromise reproductive success including gamete quality and fecundity, so too can the allocation of key proteins to detoxification reduce the availability for reproduction and hence, population replenishment.…”
Section: Discussionmentioning
confidence: 91%
“…For example, Meng et al (2022) tested human urinalysis strips on corals and found that ketone and leukocytes were reliably detected by the strips. Some of the proteins that were upregulated in corals exposed to reduced water quality, particularly toxicants, such as pesticides and polycyclic aromatic hydrocarbons (PAHs) ubiquitously detected in this study, are steroidal clearance/detoxification and regeneration enzymes that also play a role in reproduction (Rougée et al, 2006;Rougée et al, 2015;Rougée et al, 2021). Just as coral colony energetic allocation to maintenance and repair can compromise reproductive success including gamete quality and fecundity, so too can the allocation of key proteins to detoxification reduce the availability for reproduction and hence, population replenishment.…”
Section: Discussionmentioning
confidence: 91%
“…Studies with an unclear risk of bias showed no significant effect of 4-nonylphenol on several parameters such as the release of Poc. damicornis planulae, the content in cholesterol, the content in steroids (estrone, estradiol, testosterone and progesterone), and the activity of several enzymes such as the 3-beta-hydroxysteroid dehydrogenase, the cytochrome P450, the glutathione-S-transferase, and the beta-glucuronidase [75]. However, there was an increase in the activity of UDP-glycosyltransferase and a decrease in sulfotransferase 1A1 activity [75].…”
Section: Narrative Synthesis Of Study Findingsmentioning
confidence: 99%
“…damicornis planulae, the content in cholesterol, the content in steroids (estrone, estradiol, testosterone and progesterone), and the activity of several enzymes such as the 3-beta-hydroxysteroid dehydrogenase, the cytochrome P450, the glutathione-S-transferase, and the beta-glucuronidase [75]. However, there was an increase in the activity of UDP-glycosyltransferase and a decrease in sulfotransferase 1A1 activity [75]. Dispersant In the dispersant category, the exposures recorded in the narrative synthesis were also recorded in the quantitative synthesis, and only one study, which showed no statistically significant effect of Corexit 9527 on polyp retraction of Pseudodiploria strigosa, has a low risk of bias [76] (Table 9).…”
Section: Narrative Synthesis Of Study Findingsmentioning
confidence: 99%
“…Nonylphenol has an estimated half-life of 58 days within aquatic environments but this timeline can be accelerated in the presence of sunlight (Rougée et al, 2021). Although this may seem short, as NP readily binds organic matter, it can be absorbed into soil and sediment with an estimated half-life of over 60 years.…”
Section: Nonylphenol Degradationmentioning
confidence: 99%